Pengembangan Video Animasi Pada Pembelajaran IPA Kelas V Materi Perpindahan Kalor SD Negeri Kota Lubuklinggau - silvae awliyarizka (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2022)
This study aims to (a) create and develop animated video learning media in learning natural science class V Heat Transfer Material at the Elementary School Lubuklinggau City. Learning media is made by combining text, images, animation, audio, and video. (b) to measure the feasibility and practicality of animated video media in primary schoo l37 Lubuklinggau. This research is a research and development with the Borg and Gall model. The object of research is a contextual-based learning video media. The research phase includes (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) usage trial, (7) product revision, collection techniques The data used is a validation questionnaire of material experts, linguists, and presentation experts which were analyzed descriptively quantitatively. The research subjects are students of class Vprimary schoolLubuklinggau with 15 students. The results of this study are contextual-based learning video media in Learning natural Science Style material with material aspect feasibility 0.81 high validity with very valid criteria, language aspect feasibility 0.83 high validity with very valid criteria, and presentation aspect 0.80 high validity with very valid criteria. Practicality with a score of 89.27 with a percentage of 89.27% it meets the criteria of practicality. So, animated video media in learning natural Science Heat Transfer material is feasible and practical to use.